Layanan Bimbingan Klasikal untuk Meningkatkan Konsep Diri Siswa Underachiver - Rosidah, Ainur (JURNAL FOKUS KONSELING, 2017)
Abstract: The self-concept of underachiever students is studentsâ incapability in recognizing and estimating upon himself. Underachiever students are students who have high potential but high learning achievement is low or under the potential and self-concept it has. The purpose of this study is to test the effectiveness of classical guidance services to students who have self-concept of underachiever. This research uses quantitative approach, pre-experiment method with one group pretest design - posttest design. The sample of research students of Class VIII Junior High School Al-Fajar Pringsewu number was 13 students conducted by purposive sampling technique. The results showed that classical guidance services proved to be effective in improving self-concept of underachiever students.Keywords: Classical Guidance, Self Concept Student Underachiever.